Main benefits obtained from JIT implementation: empirical study in the Moroccan automotive industry. (14th January 2021) - Sebtaoui, Fatima Ezzahra; Adri, Ahmed; Rifai, Said; Sahaf, Kenza
Literature review of this research has reported 19 benefits obtained by companies as a result of a just-in-time (JIT) implementation. However, this study reduces the list of benefits using a data reduction technique in order to identify those essential factors that must be pursued. The 19 benefits are integrated in a questionnaire that is administered to 100 firms in the Moroccan automotive industry to measure the extent to which they are obtained according to companies' managers. On the one hand, a statistical validation of the questionnaire and descriptive analysis are carried out. On the other hand, an exploratory factor analysis was achieved using the principal components and varimax rotation to assure data reduction. Three main factors related to JIT benefits are identified after the factor analysis, which explain 94.980% of total variance of data. Identified factors concern production process, inventory management, and economic benefits.